(untitled) (Al-Academy, 2023)
The achievements of the art that we know today are questioned in motives that differ from what art knew before, including dramatic artistic transformations, which he called modern art.In view of the enormity of such a topic, its ramifications and its complexity, it was necessary to confine its subject to the origin of the motives of the transformations of its first pioneers, and then to stand on what resulted from that of the data of vision in composition and drawing exclusively, and through exploration in that, we got to know the vitality of change from the art of its time.And by examining the ruling contemporary philosophical concepts and their new standards and their epistemological role in contemporary life, since they include new artistic and aesthetic values, it was more useful to take them in this research to understand the consistency between thought and art in the current era, and from that the motives of modernization are an approach at the hands of the first pioneers With their homeland of innovative methods in the contemporary artistic experience